2021
DOI: 10.1016/j.jsams.2020.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fundamental movement skill proficiency among Iranian children aged 2.5–14 years

Abstract: Objectives: To determine the prevalence of fundamental movement skill (FMS) proficiency among a sample of Iranian children. Design: Cross sectional, representative sample of 2200 children aged 2.5-14 years (50% girls), living in Tehran in 2018. Methods: Trained field staff assessed 7 locomotor and 4 object control skills in educational settings using the Ohio State University Scale of Intra-Gross Motor Assessment (OSU-SIGMA). Scores for levels 1-3 represent immature performance and level 4 represents proficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…This study investigated the interplay between biological, behavioral characteristics and family SES on boys and girls FMS scores. Our model results showed that boys were generally more proficient in their FMS across all ages, a finding consistent with previous studies (Nobre et al, 2016; Nobre et al, 2018; Shams et al, 2021). These differences were greater in object control skills than in locomotion skills (Bardid et al, 2016; Pienaar et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…This study investigated the interplay between biological, behavioral characteristics and family SES on boys and girls FMS scores. Our model results showed that boys were generally more proficient in their FMS across all ages, a finding consistent with previous studies (Nobre et al, 2016; Nobre et al, 2018; Shams et al, 2021). These differences were greater in object control skills than in locomotion skills (Bardid et al, 2016; Pienaar et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The movement choices made later in life (for example, whether an individual ultimately decides to engage in exercise, physical games, sports, or even) will hinge on these FMS. Given that this stage of FMS development coincides with preschool years ( Barnett et al, 2019 ; Wainwright et al, 2019 ; Wang et al, 2020 ; Lopes et al, 2021 ; Shams et al, 2021 ) and its importance is such that preschool years are considered the golden age for motor development ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are also characterized by low fundamental movement skills (Maïano et al, 2019). While it is important to relate with the physical activity and health for children (Shams et al, 2021;Anderson et al, 2017). However, these limitations do not mean that they are not able to make good jumping movements.…”
Section: Introductionmentioning
confidence: 99%